Seasonal variation in activity and habitat use of free-ranging cattle in southern Bolivian subtropical mountain forests - Marquardt, Svenja; Alz?rreca, H.; Hillmann, Edna; Encinas, F. D.; Mayer, Andrea C.; Kreuzer, Michael (Cuban Journal of Agricultural Science, 2010)
In the present study, habitat use and activity pattern of cattle grazing unattended and unrestricted in subtropical mountain forests were assessed. The study was conducted at study sites (Meringal: M and R?o Tarija: RT) during the dry season and the following prehumid season in southern Bolivia. Adult Criollo cows (n=15) with or without calves were observed from May to July (period P1, n=19 days) and August to November (period P2, n=17 days) in 6-minute interval samplings between 8 am and 4 pm for their activity (grazing/browsing, resting, walking and other activities) in two different habitats (forest vs. riverside). The time spent grazing in the forests declined from P1 to P2 (M: 54% to 18%, P<0.01; RT: 31% to 25%, not significant), while resting at the riverbanks increased (M: 3% to 74%, P<0.001; RT: 43% to 65%, not significant; in P1 and P2, respectively). As major driving forces for these changes in activity pattern and habitat use in the two seasons, climatic factors and protection against flying insects are discussed. The results illustrate the ability of Criollo cattle in adapting to a demanding environment and changing conditions, and show the importance of river- and lakesides in such unattended transhumance systems. Key Words: Criollo, adaptation, behavior pattern, subtropical environment, extensive feeding system